Seasonality of microbial functional potentials and community diversity in high-Arctic tundra soils - Aline Frossard; Ekaterina Pushkareva; Vivien Hotter; Pascal A. Niklaus; Bjorn Tytgat; David Velazquez; Madgalene Adamczyk; Beat Stierli; Antonio Quesada; Mette M. Svenning; Ulf Karsten; Elie Verleyen; et al. (Soil Biology and Biochemistry, 2026)

Uromyces plumbarius first reported on Oenothera lindheimeri in Europe with widespread distribution and association with two common natural enemies of rust fungi - Frédéric Suffert; Kévin Meyer; Valérie Laval; Axelle Andrieux; Erik Slootweg; Pascal Frey (European Journal of Plant Pathology, 2026)

Improving sustainable crop protection using population genetics concepts - Méline Saubin; Clémentine Louet; Lydia Bousset; Frédéric Fabre; Pascal Frey; Isabelle Fudal; Frédéric Grognard; Frédéric Hamelin; Ludovic Mailleret; Solenn Stoeckel; Suzanne Touzeau; Benjamin Petre; et al. (Molecular Ecology, 2023)
Growing genetically resistant plants allows pathogen populations to be controlled and reduces the use of pesticides. However, pathogens can quickly overcome such resistance. In this context, how can we achieve sustainable crop protection? This crucial question has remained largely unanswered despite decades of intense debate and research effort. In this study, we used a bibliographic analysis to show that the research field of resistance durability has evolved into three subfields: (1) “plant breeding” (generating new genetic material), (2) “molecular interactions” (exploring the molecular dialogue governing plant–pathogen interactions) and (3) “epidemiology and evolution” (explaining and forecasting of pathogen population dynamics resulting from selection pressure[s] exerted by resistant plants). We argue that this triple split of the field impedes integrated research progress and ultimately compromises the sustainable management of genetic resistance. After identifying a gap among the three subfields, we argue that the theoretical framework of population genetics could bridge this gap. Indeed, population genetics formally explains the evolution of all heritable traits, and allows genetic changes to be tracked along with variation in population dynamics. This provides an integrated view of pathogen adaptation, in particular via evolutionary–epidemiological feedbacks. In this Opinion Note, we detail examples illustrating how such a framework can better inform best practices for developing and managing genetically resistant cultivars.

A point mutation and large deletion at the candidate avirulence locus AvrMlp7 in the poplar rust fungus correlate with poplar RMlp7 resistance breakdown - Clémentine Louet; Méline Saubin; Axelle Andrieux; Antoine Persoons; Mathilde Gorse; Jérémy Pétrowski; Bénédicte Fabre; Stéphane De Mita; Sébastien Duplessis; Pascal Frey; Fabien Halkett (Molecular Ecology, 2023)
The deployment of plant varieties carrying resistance genes ( R ) exerts strong selection pressure on pathogen populations. Rapidly evolving avirulence genes ( Avr ) allow pathogens to escape R ‐mediated plant immunity through a variety of mechanisms, leading to virulence. The poplar rust fungus Melampsora larici ‐ populina is a damaging pathogen of poplars in Europe. It underwent a major adaptive event in 1994, with the breakdown of the poplar RMlp7 resistance gene. Population genomics studies identified a locus in the genome of M . larici ‐ populina that probably corresponds to the candidate avirulence gene AvrMlp7 . Here, to further characterize this effector, we used a population genetics approach on a comprehensive set of 281 individuals recovered throughout a 28‐year period encompassing the resistance breakdown event. Using two dedicated molecular tools, genotyping at the candidate locus highlighted two different alterations of a predominant allele found mainly before the resistance breakdown: a nonsynonymous mutation and a complete deletion of this locus. This results in six diploid genotypes: three genotypes related to the avirulent phenotype and three related to the virulent phenotype. The temporal survey of the candidate locus revealed that both alterations were found in association during the resistance breakdown event. They pre‐existed before the breakdown in a heterozygous state with the predominant allele cited above. Altogether, these results suggest that the association of both alterations at the candidate locus AvrMlp7 drove the poplar rust adaptation to RMlp7 ‐mediated immunity. This study demonstrates for the first time a case of adaptation from standing genetic variation in rust fungi during a qualitative resistance breakdown.

The escalatory Red Queen: Population extinction and replacement following arms race dynamics in poplar rust - Antoine Persoons; Katherine J. Hayden; Bénédicte Fabre; Pascal Frey; Stéphane De Mita; Aurélien Tellier; Fabien Halkett (Molecular Ecology, 2017)
Host–parasite systems provide convincing examples of Red Queen co‐evolutionary dynamics. Yet, a key process underscored in Van Valen's theory – that arms race dynamics can result in extinction – has never been documented. One reason for this may be that most sampling designs lack the breadth needed to illuminate the rapid pace of adaptation by pathogen populations. In this study, we used a 25‐year temporal sampling to decipher the demographic history of a plant pathogen: the poplar rust fungus, Melampsora larici‐populina . A major adaptive event occurred in 1994 with the breakdown of R7 resistance carried by several poplar cultivars widely planted in Western Europe since 1982. The corresponding virulence rapidly spread in M. larici‐populina populations and nearly reached fixation in northern France, even on susceptible hosts. Using both temporal records of virulence profiles and temporal population genetic data, our analyses revealed that (i) R7 resistance breakdown resulted in the emergence of a unique and homogeneous genetic group, the so‐called cultivated population, which predominated in northern France for about 20 years, (ii) selection for Vir7 individuals brought with it multiple other virulence types via hitchhiking, resulting in an overall increase in the population‐wide number of virulence types and (iii) – above all – the emergence of the cultivated population superseded the initial population which predominated at the same place before R7 resistance breakdown. Our temporal analysis illustrates how antagonistic co‐evolution can lead to population extinction and replacement, hence providing direct evidence for the escalation process which is at the core of Red Queen dynamics.

Microsatellite analysis of Icelandic populations of the poplar fungal pathogen Melampsora larici-populina shows evidence of repeated colonization events - Sigridur Erla Elefsen; Pascal Frey; Halldor Sverrisson; Jón Hallsteinn Hallsson (European Journal of Plant Pathology, 2014)

A sensitive real-time PCR assay for the detection of the two Melampsora medusae formae speciales on infected poplar leaves - Anne-Laure Boutigny; Cécile Guinet; Agathe Vialle; Richard Hamelin; Pascal Frey; Renaud Ioos (European Journal of Plant Pathology, 2013)

Exploring the role of asexual multiplication in poplar rust epidemics: impact on diversity and genetic structure - Benoît Barrès; Cyril Dutech; Axelle Andrieux; Fabien Halkett; Pascal Frey (Molecular Ecology, 2012)
Fungal plant pathogens, especially rust fungi ( P ucciniales), are well known for their complex life cycles, which include phases of sexual and asexual reproduction. The effect of asexual multiplication on population genetic diversity has been investigated in the poplar rust fungus M elampsora larici‐populina using a nested hierarchical sampling scheme. Four hierarchical levels were considered: leaf, twig, tree and site. Both cultivated and wild poplar stands were sampled at two time points at the start and end of rust epidemics. A total of 641 fungal isolates was analysed using nine microsatellite markers. This study revealed that the genetic signature of asexual multiplication in the wild poplar stand was seen only at lower hierarchical levels (leaf and twig). Moreover, we observed an erosion of clonal structure through time, with an increase in both gene and genotypic diversity. New genotypes contributed to host infection over time, which demonstrates the importance of allo‐infection in the epidemic process in this host‐pathogen system. Compared with the wild stands, the nearly lack of detection of clonal structure in the cultivated stands reflects the higher infection level on cultivated poplars. More generally, this genetic analysis illustrates the utility of population genetics approach for elucidating the proportion of asexual reproduction in the multiplication of isolates during an epidemic, and for proper quantification of asexual dispersal in plant pathogens.

Disentangling the genetic origins of a plant pathogen during disease spread using an original molecular epidemiology approach - CONSTANCE XHAARD; BENOÎT BARRÈS; AXELLE ANDRIEUX; LYDIA BOUSSET; FABIEN HALKETT; PASCAL FREY (Molecular Ecology, 2012)
The advent of molecular epidemiology has greatly improved our ability to identify the population sources and track the pathogen movement. Yet the wide spatial and temporal scales usually considered are useful only to infer historical migration pathways. In this study, Bayesian genetic assignments and a landscape epidemiology approach were combined to unravel genetic origin and annual spread during a single epidemic of a plant pathogen: the poplar rust fungus Melampsora larici‐populina . The study focused on a particular area—the Durance River valley—which enabled inoculum sources to be identified and channelled spread of the epidemic along a one‐dimensional corridor. Spatio‐temporal monitoring of disease showed that the epidemic began in the upstream part of the valley and spread out downstream. Using genetic assignment tests, individuals collected at the end of the epidemic were sorted into two genetic groups; very few hybrids were detected, although individuals from both groups coexisted locally downstream in the valley. The epidemic originated from two genetically distinct inoculum sources. Individuals of each group then dispersed southwards along the Durance River and became mixed in poplar riparian stands. These two genetic groups were found previously at a wider spatial scale and proved to result from distinct evolutionary histories on either wild or cultivated poplars. This study showed that the two groups can mix during an epidemic but do not hybridize because they then reproduce asexually. In general, the methods employed here could be useful for elucidating the genetic origin and retracing the colonization history and migration pathways of recent epidemics.

Chalara fraxinea is an invasive pathogen in France - Claude Husson; Bruno Scala; Olivier Caël; Pascal Frey; Nicolas Feau; Renaud Ioos; Benoît Marçais (European Journal of Plant Pathology, 2011)

Characterization of 41 microsatellite loci developed from the genome sequence of the poplar rust fungus, Melampsora larici-populina - Constance Xhaard; Axelle Andrieux; Fabien Halkett; Pascal Frey (Conservation Genetics Resources, 2009)

Usefulness of single copy genes containing introns in Phytophthora for the development of detection tools for the regulated species P. ramorum and P. fragariae - Renaud Ioos; Lise Laugustin; Nathalie Schenck; Sylvie Rose; Claude Husson; Pascal Frey (European Journal of Plant Pathology, 2006)

SCAR–based PCR primers to detect the hybrid pathogen Phytophthora alni and its subspecies causing alder disease in Europe - Renaud Ioos; Claude Husson; Axelle Andrieux; Pascal Frey (European Journal of Plant Pathology, 2005)

Genomic Variation within Monilinia laxa, M. fructigena and M. fructicola, and Application to Species Identification by PCR - Renaud Ioos; Pascal Frey (European Journal of Plant Pathology, 2000)

Structure of Melampsora larici-populina populations on wild and cultivated poplar - Jean Pinon; Pascal Frey (European Journal of Plant Pathology, 1997)